Thermal aspects of using ash heat exchanger in scheme of complex power technology processing sulfur oil shale - A. A. Morev; A. N. Mrakin; A. A. Selivanov (Известия высших учебных заведений: Проблемы энергетики)
The application of the regenerative heat exchanger with a moving dense layer of solid heat carrier for heat recovery ash products conversion sulfur shale. The technique of hydraulic and thermal calculation of the regenerative heat exchanger with a moving dense layer, taking into account the thermal characteristics of bottom ash.